ANALISIS SWOT DALAM MENINGKATKAN EFEKTIVITAS MANAJEMEN STRATEGIS DI LEMBAGA PENDIDIKAN SEKOLAH DASAR - Pramodya Casqie Lunita; Rts. Kholifah Hidayati; Fidhiya Marlan Utami; Linardo Pratama (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the application of SWOT analysis in improving the effectiveness of strategic management in elementary schools. SWOT analysis is used as a tool to identify various internal and external factors that influence the success of educational institutions in achieving their strategic goals. Through this approach, schools can identify strengths such as competent teaching staff and adequate facilities, while simultaneously understanding weaknesses such as limited resources and lack of learning innovation. Furthermore, opportunities arising from technological developments, government support, and increasing public awareness of the importance of basic education can be optimally utilized. On the other hand, threats such as increased competition between schools and changes in the social environment need to be anticipated with appropriate strategies. The analysis results show that the application of SWOT-based strategic management enables educational institutions to develop more focused, adaptive plans that are oriented toward improving the quality of learning. With a comprehensive understanding of internal and external conditions, elementary schools are able to establish effective strategic policies to achieve the institution's vision and mission. Overall, SWOT analysis plays a crucial role as a foundation for strengthening the competitiveness, management efficiency, and sustainability of educational institutions in an era of dynamic change.